PENERAPAN SOSIODRAMA DALAM MENINGKATKAN KEMAMPUAN MENGELOLA KONFLIK REMAJA - Adam, Adam (Pusat Studi Gender dan Anak, IAIN Palu, 2019)
The process of human development is inseparable from the influence of the environment, so the development of adolescents who sit in junior high school will be different from adolescents in high school, or in college, even though human life is definitely not going to be separated from the past and the future. Adolescence is one of the development periods experienced by humans in their lives. During the transition, adolescents are in an unstable condition. There is a feeling of insecurity, because they have to change or change the behavior patterns of adolescents from children to adults. From this transition period the potential for social conflict arises, because of the desire to meet human needs. Sociodrama is one of the techniques in group guidance that aims to solve social problems that arise in human relationships that can be implemented if most group members face similar social problems, or if they want to practice or change certain attitudes. Conflicts can have positive or negative effects, and they always exist in life. The problem is how the conflict can be managed in such a way that it does not cause social disintegration. Therefore, it needs a conflict management, so that the conflict can be controlled and directed